The effects of voltage dependence and ion-binding reaction rates on a thermodynamically constrained mathematical model of the Na/Ca exchanger - Shaocong Ou; Zhongyang Xiao; Keika Oyama; Masaaki Furukawa; Yuttamol Muangkram; Yukiko Himeno; Akira Amano (Scientific Reports)
Abstract Specialized mathematical models have been proposed to quantitatively assess the ion transporter performance in heart-related physiological experiments. The Na/Ca exchanger imports three Na+ ions into the cell and exports one Ca2+ ion; therefore, it plays a vital role in cardiomyocyte ion homeostasis. The detailed characteristics of the voltage and ion concentration dependencies of the exchanger current were reported by Matsuoka and Hilgemann in 1992, whereas existing mathematical models can only reproduce a limited range of experimental data. This study primarily focuses on the development of a new mathematical model by introducing charge movements to all consecutive state transition processes under thermodynamic constraints, which accomplish voltage dependencies and current generation for each ion binding and dissociation process. The proposed model includes 22 charge movement, dissociation constant, and rate constant parameters, which were optimized to fit the voltage and ion concentration dependencies of the steady-state transporter currents. Through this process, most parameters converged effectively. Using the optimal parameters, our model successfully replicated the experimental steady-state current data as well as the transient current data. This underscores the accuracy and reliability of our model for reflecting the complex dynamics of cardiomyocyte electrophysiology.